Effect of cellular and extracellular pathology assessed by T1 mapping on regional contractile function in hypertrophic cardiomyopathy. Issue 1 (December 2017) - Swoboda, Peter; McDiarmid, Adam; Erhayiem, Bara; Law, Graham; Garg, Pankaj; Broadbent, David; Ripley, David; Musa, Tarique; Dobson, Laura; Foley, James; Fent, Graham; Page, Stephen; et al.
Abstract Background Regional contractile dysfunction is a frequent finding in hypertrophic cardiomyopathy (HCM). We aimed to investigate the contribution of different tissue characteristics in HCM to regional contractile dysfunction. Methods We prospectively recruited 50 patients with HCM who underwent cardiovascular magnetic resonance (CMR) studies at 3.0 T including cine imaging, T1 mapping and late gadolinium enhancement (LGE) imaging. For each segment of the American Heart Association model segment thickness, native T1, extracellular volume (ECV), presence of LGE and regional strain (by feature tracking and tissue tagging) were assessed. The relationship of segmental function, hypertrophy and tissue characteristics were determined using a mixed effects model, with random intercept for each patient. Results Individually segment thickness, native T1, ECV and the presence of LGE all had significant associations with regional strain. The first multivariable model (segment thickness, LGE and ECV) demonstrated that all strain parameters were associated with segment thickness (P  < 0.001 for all) but not ECV. LGE (Beta 2.603, P  = 0.024) had a significant association with circumferential strain measured by tissue tagging. In a second multivariable model (segment thickness, LGE and native T1) all strain parameters were associated with both segment thickness (P  < 0.001 for all) and native T1 (P  < 0.001 for all) but not LGE. Conclusion Impairment of contractile function in HCM is predominantly associated with the degree of hypertrophy and native T1 but not markers of extracellular fibrosis (ECV or LGE). These findings suggest that impairment of contractility in HCM is mediated by mechanisms other than extracellular expansion that include cellular changes in structure and function. The cellular mechanisms leading to increased native T1 and its prognostic significance remain to be established.